ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MTS PADA MATERI POLA BILANGAN - Nurhayati Nurhayati; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
The article research aims to find out the students' mathematical problem solving ability of MTs in West Bandung Regency with indicator of students' mathematical problem solving ability that used are identifying known data, asked data, the adequacy of the data to problem solving, identifying strategy that can be pursued, completing mathematical model is accompanied by reason, checking the truth of the solution that is obtained. This research was conducted to the 32 students in one of MTs in Kertamukti village, West Bandung Regency by using qualitative descriptive method. An instrument that is used in the form of 5 items question about problem solving ability on the material